Studying the biological activity of some Antimony Compounds with amino acids - Baghdad Science Journal (مجلة بغداد للعلوم, 2010)
In this work four complexes of antimony were prepared ,Na[SbO(gly)2],Na[SbO(Asp)2],Na[SbO(Tyrosin)2], Na [SbO(phen alanin)2]. by reaction SbOCl with salts amino acids identifiefid these complexes by FTIR ,their conductivity was measured and also their biological activity against two types of bacteria was studied ,they were biologically active.